A Praça das Mercês: Análise de um espaço livre público no Centro Histórico de São Luís (MA) - SERRA, Marcelo Ferreira (2024)
Public open spaces are configured as public spaces par excellence, characterized by the absence of physical or social barriers that restrict access, allowing any individual, regardless of age, gender, social class or origin, to enjoy the environment. Among these spaces, squares play a central role in cities, serving as places for coexistence, leisure, and social interaction, in addition to contributing to the quality of life by offering green areas and environments conducive to physical, cultural, and recreational activities. Therefore, the incorporation of these spaces into the urban fabric provides, in essence, a relevant social benefit for the population. In this context, the research aimed to analyze the social benefits of Praça das Mercês, located in the Historic Center of São Luís (MA), as a public free space designed for the leisure and conviviality of the population. Adopting a qualitative-quantitative approach, the methodological path included bibliographic review, documentary research, extensive direct observation with application of forms and intensive direct observation with interviews, and photographic records were also made with the use of a smartphone (Samsung Galaxy A34 5G model) to ratify the data. The results of the research reveal that Praça das Mercês performs several functions as a free public space. It not only fosters leisure activities and social interaction, but also contributes to urban aesthetics, income generation, reduction of social stigmas and also to keep alive the historical and cultural heritage of African peoples in the state of Maranhão. The benefits reach people of all age groups, who live both in the surroundings of the square and outside it. However, the research also identified some limitations in the space resulting from flawed and exclusionary urban planning, such as the lack of shaded areas and points of sale of foodstuffs, factors that reduce the potential of the square as a space for coexistence and leisure. In view of these results, the research highlights the importance of inclusive and continuous urban planning, which will be essential to ensure the sustainability and relevance of this public space for future generations.